Transformation in Accounting Practices - Thanasas, Georgios L.; Kampiotis, Georgios (Technium Business and Management, 2024)
This paper explores the transformative impact of automation and artificial intelligence (AI) on accounting practices. The integration of AI has shifted accounting from traditional manual tasks to automated processes, enhancing efficiency, accuracy, and scalability. AI-driven systems reduce human errors, ensure compliance, and offer data-driven insights, enabling accountants to take on more strategic advisory roles. Additionally, the adoption of cloud-based solutions allows real-time financial data access, improving decision-making processes. Through a review of real-world applications and the potential challenges, this paper highlights how AI is reshaping financial reporting, auditing, and the future of the accounting profession.